A practical leader-follower tracking control scheme for multiple nonholonomic mobile robots in unknown obstacle environments - Wang, Yuanzhe (2020)
This brief addresses the leader-follower (L-F) tracking control problem for multiple nonholonomic mobile robots in unknown obstacle environments. Unlike most of the existing approaches investigating similar problems, a series of practical issues is considered and tackled in the proposed scheme. For leader tracking, a class of bounded barrier functions are employed to formulate distance and bearing angle constraints introduced by sensor limitations and L-F collision avoidance requirement. To ensure robot safety in unknown environments, a multiregion obstacle avoidance algorithm is proposed which prioritizes different control objectives in different regions. This brief also studies the leader-loss situation, which may be caused by illumination variation, motion blurring, or visual occlusion by obstacles. To deal with this case, a fault-tolerant strategy is designed to drive $F$ to the place where $L$ was lost immediately. The control scheme proposed in the brief is primarily designed for a communication-free environment where only local state measurements are available. Furthermore, it has control input constraints explicitly taken into account. Real robot experiment has been performed to validate the proposed method.